A dynamic model for assessing soil denitrification in large-scale natural wetlands driven by Earth Observations. (December 2022) - Martínez-Espinosa, Columba; Sauvage, Sabine; Al Bitar, Ahmad; Sánchez Pérez, Jose Miguel
Abstract: The Wetland Soils Denitrification Model (WSDM) developed here for natural wetlands, is a physical based model that proposes: (i) the inclusion of soil moisture and temperature from satellite-based Earth Observations at diurnal temporal resolution and (ii) the distinction of soils under different wetland typologies (i.e., flooded forests, freshwater marshes, brackish wetlands, peatlands, and complex wetlands). Despite uncertainties involved, these two features are key to upscale nitrification/denitrification dynamics in natural wetlands at landscape, regional and global scales. In this study, the performance of WSDM was validated with soils in flooded forests and freshwater marshes in the central Amazonian floodplain. WSDM multiannual time series (2012–2019) show that climate anomalies intensify denitrification events. Flooded forests were identified with the highest annual denitrification rates. Annual denitrification and N2 O emissions estimated in this study are in line with previous studies. Highlights: A novel large-scale dynamic model for wetlands driven by satellite data is presented. Temperature and soil moisture are key to shape denitrification dynamics. Earth Observation data are advantageous when no field data is available.